2003
DOI: 10.1590/s0041-87812003000200005
|View full text |Cite
|
Sign up to set email alerts
|

Gastric myoelectrical activity in neonates of different gestational ages by means of electrogastrography

Abstract: PURPOSE: to describe the patterns of the gastric myoelectrical activity, pre-and postprandially, in clinically stable neonates of different gestational ages, during their first two weeks of life by means of Electrogastrography. PATIENTS AND METHODS:Electrogastrography was recorded in forty-five clinically stable neonates of different gestational ages (group I: 15 neonates of > 37 weeks, group II: 15 premature neonates of 32-37 weeks; Group III: 15 premature neonates of 28-31 weeks) receiving intermittent enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
(16 reference statements)
1
4
0
Order By: Relevance
“…Although multicenter studies must be conducted to establish normative values, we defined % tachygastria as 35%-45% in our cohort (1 SD from the mean). We demonstrated that the preterm infant stomach spends a large % of time in tachygastria and we confirmed this is more common in neonates than older children and adults (24)(25)(26), suggestive of GI immaturity (6,7). We also confirmed that preterm infants had similar % tachygastria when compared to term infants.…”
Section: Discussionsupporting
confidence: 77%
“…Although multicenter studies must be conducted to establish normative values, we defined % tachygastria as 35%-45% in our cohort (1 SD from the mean). We demonstrated that the preterm infant stomach spends a large % of time in tachygastria and we confirmed this is more common in neonates than older children and adults (24)(25)(26), suggestive of GI immaturity (6,7). We also confirmed that preterm infants had similar % tachygastria when compared to term infants.…”
Section: Discussionsupporting
confidence: 77%
“…Numerous researchers have demonstrated that the infant's gastrointestinal mucosal membrane is immature. 17,[20][21][22][23] The mucous membrane of the neonatal gut is not a closed system. It is able to absorb large macromolecules to facilitate transfer of passive immunity from the mother's milk.…”
Section: Immaturity Of the Gastrointestinal Mucosal Barriermentioning
confidence: 99%
“…In this study, we have implemented a unique and novel method for quantifying the % time spent in each GR frequency band during each sub-feeding period using continuous wavelet transform, CWT. Previous literature has suggested the use of running spectral analysis methods, such as short-term Fourier transform (FT) analysis 15,[31][32][33][34] . CWT is useful in analyzing the non-stationary signal and also allows to filter out stationary and non-stationary signals 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…al. reported no significant difference in % normogastria between term and preterm neonates in the pre-and post-feed periods 15 . Ortigoza et.…”
mentioning
confidence: 95%
See 1 more Smart Citation